Stromelysin Activity in Canine Cranial Cruciate Ligament Rupture - Spreng, D.; Sigrist, Nadja; Busato, A.; von Rechenberg, Brigitte; Schawalder, P. (Veterinary and Comparative Orthopaedics and Traumatology, 1999)
The goal of our study was to compare values of stromelysin activity in stifle joint tissues, from dogs with osteoarthritis, secondary to naturally acquired cranial cruciate ligament (CCL) rupture and from a control population.Twenty four dogs (CCL group) with osteoarthritis (OA), secondary to CCL rupture, were evaluated. The control groups consisted of 22 beagles (control #1) and 14 dogs (control #2) without CCL rupture. Articular cartilage, synovial membrane and CCL tissue specimens were harvested during operations in the CCL group and immediately following euthanasia in the control groups. The specimens were submitted for routine histology and for explant tissue cultures.Stromelysin activity was measured in the supernatant of explanted cultures. The results of stromelysin concentrations were reported as mean ± STD and compared to histological cartilage degeneration, synovial membrane inflammation and ligament changes. Stromelysin activity in cartilage explants of the CCL group (70 ± 82.5 U/g) was significantly higher when compared to the control #1 (4.2 ± 6.3 U/g) and control #2 (15 ±10 U/g) groups. The synovial membrane explant cultures of the CCL group produced less stromelysin compared to the control group. Whereas ligament cultures showed a tendency toward higher activity of stromelysin when compared to the control groups. An association between the severity of histological OA changes in the cartilage and stromelysin activity in cartilage explants was demonstrated. We conclude that dogs with OA, secondary to naturally acquired CCL rupture, release higher stromelysin levels in articular cartilage and cranial cruciate ligament explant cultures when compared to the controls. Our results indicate that stromelysin production in articular cartilage is related to the severity of OA.Stromelysin, one of the major metalloproteinases degrades articular cartilage mainly by cleavage of proteoglycans. Increased levels of stromelysin could be demonstrated in cartilage of stifle joints from dogs with naturally acquired cranial cruciate ligament rupture using a radioimmunoassay. There was an indication in this study that the activity of stromelysin is associated with the severity of osteoarthritic changes.Presented in part at the European College of Veterinary Surgeons Annual Scientific Meeting, Pörtschach-Austria, June 1998.
Keywords: Osteoarthritis; cartilage; stromelysin; dog